Wilson disease in a Bangladeshi child: A case report (Bangladesh Medical Journal, 2016)
Wilson disease, also known as hepatolenticular degeneration results from improper metabolism of copper due to deficiency or low level of caeruloplasmin which causes excessive accumulation of copper in liver, brain, eyes and different organs. This is not a curable disease. The patient needs a lifelong treatment but early diagnosis can prevent significant damage to the critical organs. This article presents a case study on Wilson disease and the role of radiology in helping to diagnose the disease and monitor patients with this condition.Bangladesh Med J. 2016 Jan; 45 (1): 54-56